2003
DOI: 10.1161/01.atv.0000082689.46538.df
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Expression of the CysLT2Receptor Accounts for Calcium Signaling by Cysteinyl Leukotrienes in Human Umbilical Vein Endothelial Cells

Abstract: HUVECs almost exclusively express the CysLT2R. Furthermore, Ca2+ fluxes elicited by CysLT in these cells emanate from perturbation of the CysLT2R, rather than the expected CysLT1R. Hence, signaling events involving CysLT2R might trigger functional responses involved in the critical components of LT-dependent vascular reactions, which in turn have implications for ischemic heart disease and myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…The importance of CysLT 2 receptor in endothelial cells has been reported. CysLT 2 receptors are highly expressed in HUVECs (39) and mediate the increased intracellular Ca 2+ and vascular permeability induced by LTD 4 or LTC 4 (40). They also mediate the up-regulated expression of early genes after a brief exposure (1 h) to LTD 4 , such as early growth response (EGR) and nuclear receptor subfamily 4 group A transcription factors, E-selectin, CXC ligand 2, and IL-8; none of effects can be blocked by selective CysLT 1 -receptor antagonists (8).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CysLT 2 receptor in endothelial cells has been reported. CysLT 2 receptors are highly expressed in HUVECs (39) and mediate the increased intracellular Ca 2+ and vascular permeability induced by LTD 4 or LTC 4 (40). They also mediate the up-regulated expression of early genes after a brief exposure (1 h) to LTD 4 , such as early growth response (EGR) and nuclear receptor subfamily 4 group A transcription factors, E-selectin, CXC ligand 2, and IL-8; none of effects can be blocked by selective CysLT 1 -receptor antagonists (8).…”
Section: Discussionmentioning
confidence: 99%
“…Exon III of the mouse CysLT 1 receptor gene contains an in-frame start codon (ATG) that is 39-bp upstream of the ATG translation start site reported for the human CysLT 1 receptor. This sequence permits a 13-aa extension at the N terminus, resulting in a long receptor isoform with 352 deduced amino acid residues and a calculated mass of 40,715. The N-terminal extension is missing in the human CysLT 1 receptor because of a stop codon six nucleotides upstream of the ATG start codon within the coding exon; thus, only one isoform of the CysLT 1 receptor exists in the human (35).…”
Section: Molecular Biology Of the Cyslt 1 And Cyslt 2 Receptorsmentioning
confidence: 99%
“…Especially strong hybridization was noted in interstitial macrophages in the lung (37). Both HUVEC (40) and coronary smooth muscle cells (41) both express high levels of the CysLT 2 receptor protein and mRNA, suggesting a prominent function for this receptor in vascular responses. A single nucleotide polymorphism in the human CysLT 2 receptor was reported that results in the substitution of methionine for valine at amino acid residue 202.…”
Section: Molecular Biology Of the Cyslt 1 And Cyslt 2 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CysLTR2 is highly expressed in heart, coronary vessels, and different regions of brain, with lower expression present in peripheral blood cells. It has been shown that CysLTR2 is expressed on human endothelial cells (8,9), and its activation may be responsible for P-selectin surface expression (10), von Willebrand factor secretion (11), and enhanced vascular permeability (12). Early studies have shown that LTC 4 and LTD 4 are very potent arteriole constrictors and inducers of plasma leakage and leukocyte adhesion, suggesting a significant role of CysLTR2 in regulation of the circulation (13).…”
Section: Ifn-␥ Induces Cysteinyl Leukotriene Receptor 2 Expression Anmentioning
confidence: 99%